Recurring Job Optimization in Scope - Bruno, Nicolas; Kandula, Srikanth; Shi, Bing; Wu, Ming-Chuan; Zhou, Jingren (SIGMOD '12, 2012)
An increasing number of applications require distributed data storage and processing infrastructure over large clusters of commodity hardware for critical business decisions. The MapReduce programming model [2] helps programmers write distributed applications on large clusters, but requires dealing with complex implementation details (e.g., reasoning with data distribution and overall system configuration).